A Mastery Approach to Complex Esophageal Diseases (Springer International Publishing, 2018)
This book brings together all stages of the diagnosis and treatment of all complex esophageal disorders in a single volume. A special emphasis is given to emerging procedures in laparoscopy, thoracoscopy, and endoscopy. Stages of operative approaches with relevant technical considerations are outlined in an easily understandable manner. The text is illustrated throughout by easy to understand illustration line graphs that depict fundamental anatomic or technical principles. Each chapter includes a summary of the current management strategy for the disease process, and a review of current innovations surrounding the topic. The book is applicable to physicians in both the surgical disciplines and in gastroenterology, as well as residents and fellows in this area.